Be different - the diversity of peroxisomes in the animal kingdom - Islinger, Markus; Cardoso, M. J. R.; Schrader, Michael (Biochimica et biophysica acta. Molecular cell research, 2010)
Peroxisomes represent so-called “multipurpose organelles” as they contribute to various anabolic as well as catabolic pathways. Thus, with respect to the physiological specialization of an individual organ or animal species, peroxisomes exhibit a functional diversity, which is documented by significant variations in their proteome. These differences are usually regarded as an adaptational response to the nutritional and environmental life conditions of a specific organism. Thus, human peroxisomes can be regarded as an in part physiologically unique organellar entity fulfilling metabolic functions that differ from our animal model systems. In line with this, a profound understanding on how peroxisomes acquired functional heterogeneity in terms of an evolutionary and mechanistic background is required. This review summarizes our current knowledge on the heterogeneity of peroxisomal physiology, providing insights into the genetic and cell biological mechanisms, which lead to the differential localization or expression of peroxisomal proteins and further gives an overview on peroxisomal biochemical pathways, which are specialized in different animal species and organs. Moreover, it addresses the impact of proteome studies on our understanding of differential peroxisome function describing the utility of mass spectrometry and computer-assisted algorithms to identify peroxisomal target sequences for the detection of new organ- or species-specific peroxisomal proteins.
Available online 27 March 2010
Gesehen am 30.06.2023